2012
DOI: 10.32385/rpmgf.v28i2.10928
|View full text |Cite
|
Sign up to set email alerts
|

Vacina da varicela na infância

Abstract: INTRODUÇÃO A varicela é uma infecção altamente contagiosa, causada pelo vírus varicela-zoster (VVZ) e caracteriza-se por um exantema pápulo-vesicular pruriginoso. 1 Segundo dados norte-americanos anteriores à introdução da vacina, mais de 90% dos casos ocorriam antes dos 15 anos de idade, com maior incidência entre os 5 e os 9 anos. 2 Na maioria das crianças a varicela evolui de forma benigna e auto-limitada, mas pode apresentar complicações graves, nomeadamente sobre-infecção bacteriana cutânea, complicações … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(49 citation statements)
references
References 13 publications
(24 reference statements)
0
49
0
Order By: Relevance
“…A meta-analysis was conducted in two reviews, 21,22 with a further review providing a narrative synthesis of findings. 36 All three reviews reported consistent findings of evidence that two-dose vaccination is more efficacious/effective in preventing varicella. The full findings have been provided in the supplementary material (Appendix D).…”
Section: Two-versus One-dose Varicella Vaccinationmentioning
confidence: 63%
See 2 more Smart Citations
“…A meta-analysis was conducted in two reviews, 21,22 with a further review providing a narrative synthesis of findings. 36 All three reviews reported consistent findings of evidence that two-dose vaccination is more efficacious/effective in preventing varicella. The full findings have been provided in the supplementary material (Appendix D).…”
Section: Two-versus One-dose Varicella Vaccinationmentioning
confidence: 63%
“…27 These estimates are supported from findings from reviews that provided a narrative synthesis of the effectiveness of one-dose varicella vaccination. 7,32,35,36 The evidence also suggests that onedose vaccination strategies are highly effective against moderate to severe varicella with effectiveness estimates ranging from 90% to 100%. 20,26,35,36 Estimates of the effectiveness of two-dose varicella vaccination strategies (from reviews that conducted a meta-analysis) to prevent varicella of any severity were less variable, ranging from 87% to 95%, 20 with similar estimates for outbreak settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the 17 reviews that assessed safety provided a meta‐analysis, 24,29,32,33 two of which included a meta‐analysis of RCT data 24,29 . The remaining 13 reviews provided a narrative summary of findings 23,25–28,30,31,34–39 . None of the 17 reviews had a geographic limitation.…”
Section: Resultsmentioning
confidence: 99%
“…Another review, conducted at the same time, noted international experience suggesting that fever and mild papulovesicular rash are possible adverse effects of the vaccine 30 . In a third review, it was reported that 47.7% of vaccinees (RCT including 507 children vaccinated for varicella) had at least one adverse effect related to the vaccine (most of minor or medium intensity) with fever the most frequent systemic adverse event with a verified relationship with the vaccine 26 . The same review reported results from an observational study covering a 10 year period in the USA.…”
Section: Resultsmentioning
confidence: 99%